Design of robust constant beamwidth beamformer with maximal sparsity - Kai WU; Tao SU; Qiang LI; Xue-hui HE (Tongxin xuebao)
To reduce the complexity of broadband array systems,an optimization model was built based on the analysis of the sparsity of the broadband array.The objective function was the convex combination of sensor and TDL sparsity with the constraint of constant beamwidth.By re-weighting the objective function,the sparsity of the array weights in-creased and converged to the maximal value.The equivalence between the norm constraint on array weights and the spar-sity of TDL was proved.Simulation results demonstrate that to obtain the same performance,the number of sensors and TDL of the proposed beamformer needed is decreased which reduces the system complexity,showing that the beam-former designed has great practical value.